Cytotoxic Effects of Eupatorium cannabinum on MCF-7 Human Breast Cancer Cell Line - Morteza Abuali; Mohammad Reza Shams Ardekani*; Hassan Rezadoost; Mahdi Vazirian; Majid Balaei-Kahnamoei; Maryam Hamzeloo-Moghadam (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Cancer is known to be the second cause of death around the world. The most prevalent cancer among women is breast cancer. Use of plant-derived products in cancer treatment may reduce adverse side effects. Extensive research around the world has led to the discovery of herbal compounds that can be used to treat some types of cancer. According to previous studies, the methanol extract of Eupatorium cannabinum has shown cytotoxic effects in some cancer cell lines. In the present study, bioassay guided fractionation and isolation was conducted on E. cannabinum to evaluate the cytotoxic activityin MCF-7 breast cancer cell line. Methods: The Extraction from theaerial parts was performed by maceration method. Isolation and purification of the extracts were performed by column chromatography. The cytotoxic activity of different extracts of E. cannabinum was evaluated against MCF-7 cell line by MTT assay and a compound was isolated according to bioassay guided fractionation. The cytotoxic activity and apoptotic property of the isolated compound was determined. Results: The chloroform extract was the most active one with IC50 of 21.39±3.24 μg/mL followed by the n-hexane and methanol extracts with IC50values of 60.23±2.16 μg/mL and 81.74±3.41 μg/mL, respectively. IC50 of subfractions (1-6) from the chloroform extract were 60.83±2.56 μg/mL, 58.93±2.73 μg/mL, 37.5±3.65 μg/mL, 7.86±1.34 μg/mL, 10.61±2.34 μg/mL and 13.77±4.17 μg/mL, respectively. Eucannabinolide, a sesquiterpene lactone, was isolated from the chloroform extract according to bioassay guided fractionation. Its IC50 was found to be 13±2.45 μg/mL. Eucannabinolide induced 46.91% apoptosis at concentration of 13 μg/mL in MCF-7 cell line in Annexin V/PI assay. Conclusion: Eucannabinolideis a promising candidate for further breast cancer drug discovery studies.